Improvement of surgical treatment of an acute biliary pancreatitis at elderly and senile patients - V. I. Midlenko; A. L. Charyshkin; O. V. Midlenko; I. I. Midlenko; V. Yu. Shchegolev (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2010)
Aim of investigation. To estimate various variants of surgical treatment of acute biliary pancreatitis at patients of over 60 years old, to develop a method of cholecystectomy at the large Hartmann pouch adherent to biliary tracts, to decrease such complications, as bleeding, bile leakage, damage (intersection) of common bile or common hepatic duct.Material and methods. Patients separated into 3 groups in relation to operative access. The first group – (67 patients) was operated by traditional surgical access. The second group (54 patients) was operated through miniaccess with the help of «Generalpurpose frame wound retractor», of them 34 patients with large Hartmann pouch adherent to biliary tracts, were operated by the proposed method (patent of the Russian Federation #2358663 under application #2008103639, priority 30.01.08; registered on 20.06.2009; bulletin #17). The third group (61 patients) was operated by laparoscopic method. The mean age of patients in groups was 73,1 years. In 100% of cases patients had two and more concomitant diseases. The main type of surgical intervention in groups – was cholecystectomy, drainage of common bile duct by Pikovsky, drainage of abdominal cavity.Results. At traditional cholecystectomy postoperative complications develop at 44,8% of patients: eventration – 7,5%, subphrenic abscess – 6%, suppuration of postoperative wound – 11,9%, pneumonias – 8,9%, pancreatonecrosis – 10,4%. After minilaparotomy in postoperative period at 9,3% of patients following complications developed: incompetence of cystic duct stump and bile leakage – 3,7%, suppurations of postoperative wounds – 3,7%, pneumonia – 1,9%. Conversions were registered in the main group at 5,6 % of patients. After videolaparoscopy complication were observed at 14,8 % of patients: damage of common bile duct, postoperative bile leakage – 3,3%, incompetence of stump of cystic duct – 1,6%, residual choledocholithiasis with accompanying obstructive jaundice – 3,3%, pancreatonecrosis – 6,6%.Conclusions. The proposed method of cholecystectomy at large Hartmann pouch adherent to biliary tracts, allows to decrease such complications as bleeding, bile leakage, excludes damage of common bile duct.